The Effect of Logistics Performance on Manufacturing Exports: A Case Study of Asia Pacific Economic Cooperation (APEC) Countries 2010-2018 - Saputri, Estining Galih; Widodo, Wahyu (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study aims to analyze the effect of logistics performance on manufacturing export in 18 members of Asia-Pacific Economic Cooperation (AEPC) during 2010-2018 period. Logistics performance was represented by the Logistics Performance Index published by the World Bank biennially. This study uses panel data regression method to see the effects of LPI overall, each component of LPI, Gross Domestic Product (GDP) Per capita, total population, and real exchange rate on manufacturing export. The result showed that the LPI overall had no significant effect on manufacturing export in 18 APEC's members. However, the estimation of each component shows significant result. Custom, Infrastructure, and Logistics Quality and Competence have a significant positive effect. Meanwhile, Shipment has no significant effect, and Tracing, Timeliness components showed significant negative effect.